Teachers and trainers in a changing world : building up competences for inclusive, green and digitalised vocational education and training (VET) ; Germany - Huismann, Adrienne [Verfasser]; Hippach-Schneider, Ute [Verfasser] (My University, 2022)
"In view of emerging issues during the last decade like digitalisation of the world of work, growing diversity following immigration, and environmental crisis, the COVID 19 pandemic accelerated the need to adapt to these new demands also in the professional development of trainers and teachers, by developing and acquiring digital skills as well as skills on sustainability and inclusiveness. In 2015-16, important VET policy programmes were initiated in these emerging fields: the overarching initiative VET 4.0 to face the challenge of digitalisation, the BBNE funding programme on sustainable development in VET (1), and the Alliance for initial and further training as well as the Educational Chains initiative to address early leaving, inclusiveness and mismatch in apprenticeship. These broad policy initiatives have already implemented numerous funding priorities and sustainable projects and were consolidated under the overarching governmental strategy ‘Pact for VET’ since 2017. One of its priorities is the continuous professional development (CPD) of trainers and VET teachers to enable them to face the challenges of digitalisation and diversity of apprentices. After giving an overview of the main types of VET teaching and training staff at the different learning environments (Chapter 2), Chapter 3 presents the initial and continuing education and training of VET school teachers, followed by Chapter 4, which describes the professional development of in-company trainers. Chapter 5 illustrates the cooperation between the IVET learning venues to support the professional development of teachers and trainers. National funding programmes and initiatives on CPD of VET staff in the fields of digitalisation, sustainability and inclusiveness are described in Chapter 6. Finally, Chapter 7 presents national surveys of teaching and training populations." (Author's abstract ; BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; P 3.2.1 Ausbilder; P 3.2.3 Lehrer; 370; Bildungspersonal; Ausbilder; Berufsschullehrer; Professionalisierung; Weiterbildung; Digitalisierung; Digitalkompetenz; Nachhaltige Entwicklung; Green skills / grüne Kompetenzen